If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 3 = -12 + 4x Reorder the terms: 3 + -1x = -12 + 4x Solving 3 + -1x = -12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3 + -1x + -4x = -12 + 4x + -4x Combine like terms: -1x + -4x = -5x 3 + -5x = -12 + 4x + -4x Combine like terms: 4x + -4x = 0 3 + -5x = -12 + 0 3 + -5x = -12 Add '-3' to each side of the equation. 3 + -3 + -5x = -12 + -3 Combine like terms: 3 + -3 = 0 0 + -5x = -12 + -3 -5x = -12 + -3 Combine like terms: -12 + -3 = -15 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| (8x^2)+2x=0 | | 6x+2=37+x | | 161/4= | | 5(x-2)+3x=6 | | 28+16x=-7x-14 | | -15-1.5= | | 16x--7x= | | -3x-9=6x+18 | | 12-y=2x-5 | | 6(2x+4)=48 | | 2-x=6x+51 | | 540+3k=7k | | 4+9lnx=3 | | 0.5x^2=0.5x+6 | | 5.61-8.94m=3.76+4.86 | | 62+11=h | | 14-(2q+5)=-5q+9 | | x^2+2x+1=x^2+3 | | 5x-24x+3=9 | | 2x(x-4)-x(2x+5)=52 | | 3(x+2)-10x=18 | | 8(2a+1)=4(7a+8) | | 6=-14+5r | | -4x-6x=-110 | | 2(2.3-6.6)= | | 5.61-8.49m=3.76m+4.86 | | -8+x=5 | | x+4.4=7.63 | | u+2.41=8.15 | | y=-7x^2-77x-126 | | 10n+12=2(5n+6) | | 2x*-x= |